Proceedings of the COVid-19 Empirical Research (COVER) Conference: Milan, Italy, October 30th, 2020 - Elia Biganzoli; Giancarlo Manzi; Alessandra Micheletti; Federica Nicolussi; Silvia Salini (Milano University Press, 2022)
The Covid-19 pandemic has spread across the world at a rate never seen before, affecting different countries and having a huge impact not only on health care systems but also on economic systems. Never as in this situation the continuous exchange of views between scientists of different disciplines must be considered the keystone to overcome this emergency. The dramatic global situation has prompted many researchers from different fields to focus on studying the Covid-19 pandemic and its economic and social implications in a multi-facet fashion. This volume collects the contributions to the COVid-19 Empirical Research (COVER) Conference, organized by the Centre of Excellence in Economics and Data Science of the Department of Economics, Management and Quantitative Methods, University of Milan, Italy, October 30th, 2020. This conference aimed to collect different points of view by opening an interdisciplinary discussion on the possible developments of the pandemic. The conference contributions ranged in the social, economic and mathematical-statistical areas.
Keywords: 300; Covid-19; Pandemic; Forecasting; Health Care Management; Virus; Resilience; Sars-Cov-2